2013 American Control Conference 2013
DOI: 10.1109/acc.2013.6580652
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear observer design for turbocharger in a SI engine

Abstract: Estimation of major turbocharger variables is essential for proper control and monitoring of a turbocharged engine. This work presents a novel algorithm to estimate turbocharger rotator speed, air temperature downstream a compressor and flow rate over the compressor using mean value models of engine subsystems. A nonlinear Luenberger observer is designed for a 1.7-lit gasoline turbocharged engine. The designed observed is shown analytically to be asymptotically stable. Performance of the designed observer is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Where x 1 is the boost pressure, x 2 is the rotor speed, u is the turbine power and K i is the output error injection gain. Using Lyapunov direct method in [19] it is shown that the estimation error vector, x x e  ˆ asymptotically approaches zero by selecting proper values for K 1 and K 2 . The extracted turbine power used in the observer is calculated from the following equation:…”
Section: Turbocharger Nonlinear Observermentioning
confidence: 99%
See 2 more Smart Citations
“…Where x 1 is the boost pressure, x 2 is the rotor speed, u is the turbine power and K i is the output error injection gain. Using Lyapunov direct method in [19] it is shown that the estimation error vector, x x e  ˆ asymptotically approaches zero by selecting proper values for K 1 and K 2 . The extracted turbine power used in the observer is calculated from the following equation:…”
Section: Turbocharger Nonlinear Observermentioning
confidence: 99%
“…A MVM estimation approach is used for modeling the turbine flow without using common inaccurate assumption of having a same pressure drop over the two nozzles in the turbine model. To illustrate application of the model for engine control and monitoring, the turbine model is used in a turbocharger observer designed from [19] to complete the estimation algorithm presented there for the turbocharger variables. Both the turbine model and the turbocharger observer are verified against the experimental data collected from an engine running in a test cell.…”
Section: Control Oriented Modeling Of a Radial Turbine For A Turbochamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the map is not suitable for analytical works like stability investigation for an estimation algorithm such as presented in Ref. [18]. Dimensional analysis is applied to the compressor map for estimating the compressor speed, reducing the interpolation error.…”
Section: Compressor Rotational Speed Estimationmentioning
confidence: 99%
“…The compressor speed model can replace existing models to improve accuracy of estimation algorithms presented in Refs. [7,18]. The proposed models for the turbocharger main variables are easy to be calibrated on a new engine for possible control and monitoring applications.…”
Section: Introductionmentioning
confidence: 99%